2018
DOI: 10.1177/0363546518810527
|View full text |Cite
|
Sign up to set email alerts
|

Professional Athletes Are Not at a Higher Risk of Infections After Anterior Cruciate Ligament Reconstruction: Incidence of Septic Arthritis, Additional Costs, and Clinical Outcomes From the French Prospective Anterior Cruciate Ligament Study (FAST) Cohort

Abstract: Background: The rate of septic arthritis in the knee after anterior cruciate ligament (ACL) reconstruction varies in the literature but is generally less than 1%. It has been reported to be higher in professional athletes (5.7%). Purpose: The primary goal was to evaluate the rate of septic arthritis after ACL reconstruction in professional athletes compared with other patients. The secondary goals were to analyze the risk factors; increased cost of infections; return to sport, satisfaction, and functional resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…There was no significant difference in the other functional knee scores or in patient satisfaction (Table 5). Table 2 Surgical data for ACL reconstruction (1) Hamstring tendon, (2) Bone-patellar tendon-bone, (3) Combined fasciae latae for intra-and extraarticular anterior cruciate ligament reconstruction, (4) Tensor fasciae latae tendon…”
Section: Functional Knee Scores At 1 Year Of Follow-up and Patient Samentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in the other functional knee scores or in patient satisfaction (Table 5). Table 2 Surgical data for ACL reconstruction (1) Hamstring tendon, (2) Bone-patellar tendon-bone, (3) Combined fasciae latae for intra-and extraarticular anterior cruciate ligament reconstruction, (4) Tensor fasciae latae tendon…”
Section: Functional Knee Scores At 1 Year Of Follow-up and Patient Samentioning
confidence: 99%
“…Type of graft HS (1) 977 (82.5%) 352 (71.8%) < 10 −4 BPTB (2) 115 (9.7%) 38 (7.8%) CFL (3) 92 (7.8%) 100 (20.4%) Extraarticular tenodesis (FLT (4) Factors favouring the return to the preinjury sport Univariate analysis showed that compared to patients who did not return to their preinjury sport at the 1-year follow-up, patients who did return to their preinjury sport were significantly younger and lighter, were professional or competitive athletes without a prior history of knee surgery, had better preoperative functional and psychological scores (subjective IKDC, KOOS daily life, sports and quality of life, Lysholm and ACL-RSI), belonged to the "with vancomycin" group, underwent associated extraarticular reconstruction, presented with fewer medial meniscal lesions, and did not present with complications during the first year after surgery, in particular septic arthritis ( Table 6). The final multivariate analysis included the study group (1 or 2), age under 25, male gender, competitive or professional sport, a history of knee surgery, preoperative scores (subjective IKDC ≥ 65, KOOS daily life ≥ 85, KOOS sport ≥ 70, KOOS quality of life ≥ 40, ACL-RSI ≥ 55), the association of extraarticular reconstruction, the presence of a medial meniscal tear, the development of a severe complication during the first year (including an infection and a homolateral retear).…”
Section: Functional Knee Scores At 1 Year Of Follow-up and Patient Samentioning
confidence: 99%
“…The PubMed search strategy yielded 4 eligible studies, 3,17,27,32 from which data were extracted and included in the pooled data analysis with the current study. The pooled study population comprised 11,416 patients, including 1118 professional athletes.…”
Section: Literature Search and Pooled Data Analysismentioning
confidence: 99%
“…14,22,26,32,36 In contrast to these previous reports, 2 recent series did not identify a significant difference in the rate of SA between professional and nonprofessional athletes. 3,17 These conflicting findings may have been due to the fact that previous studies were underpowered.…”
mentioning
confidence: 99%
“…Despite there being many reports on the surgical procedure for knee ligament reconstruction, Original especially the anterior cruciate ligament determination of burr hole positions, selection of tendon grafts, and so on [1][2][3][4][5][6][7][8][9][10][11] , there have been few reports on infection prevention [12][13][14][15][16][17][18][19][20][21][22] and no reports on the sterilization of reconstruction materials using povidone-iodine during the surgical procedure. We have previously reported on the surgical procedure and outcomes of knee ligament reconstruction 23 .…”
Section: Introductionmentioning
confidence: 99%